Democratic Policing before the Due Process Revolution - Seo, Sarah A. (2019)
According to prevailing interpretations of the Warren Court’s Due Process Revolution, the Supreme Court constitutionalized criminal procedure to constrain the discretion of individual officers. These narratives, however, fail to account for the Court’s decisions during that revolutionary period that enabled discretionary policing. Instead of beginning with the Warren Court, this Essay looks to the legal culture before the Due Process Revolution to provide a more coherent synthesis of the Court’s criminal procedure decisions. It reconstructs that culture by analyzing the prominent criminal law scholar Jerome Hall’s public lectures, Police and Law in a Democratic Society, which he delivered in 1952 on the differences between democratic and totalitarian police forces. Hall’s definition of democratic policing appealed to self-rule, then to the rule of law, and finally, to due process, as he struggled to account for twentieth-century police forces that were not, in important ways, governed by the people or entirely constrained by law. Hall ultimately settled on the idea that in a democratic society due process meant that the police did not decide the outcome of a “fair trial”—a definition that is different from today’s understanding of due process, which emphasizes judicial review of police action. The Essay applies the methodology of cultural history to argue that during the Cold War, Hall articulated a concept of due process that was not just a legal norm but also a cultural value that rationalized discretionary policing and served to distinguish two competing systems of government that both relied on discretionary authority. The Essay concludes by exploring how Hall’s explication of due process, which was representative of midcentury views, might revise standard accounts of the Due Process Revolution. Understanding the legal culture that came before—and informed—the Warren Court’s criminal procedure decisions suggests that due process functioned as much to justify as to restrain police discretion